Metody reprezentacji wiedzy agentów w multiagenckich systemach wspomagających podejmowanie decyzji finansowych - Sobieska-Karpińska, Jadwiga; Hernes, Marcin (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The article presents structure of agents knowledge representation in multiagents systems aiding financial decisions. Definition of agent, model of agents programme in BDI architecture and definition of agents knowledge's structure are presented. The structure considers contribution of decisions elements at the whole of decision and it considers rank of certain agents opinions. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 232-237